Пошаговое объяснение:
cos² x/2 - sin² x/2 ≥- √3/2
cos² x/2 - (1-cos² x/2) ≥- √3/2
cos² x/2 - 1+cos² x/2 ≥- √3/2
2cos² x/2 ≥ 1 - √3/2
cos² x/2 ≥ 1/2 - √3/4
cos² x/2 ≥0,067 ±√ из обеих частей и потом применим арккосинус
cos x/2 ≤- 0,2588 cos x/2 ≥0,2588
105°+720°к≤ x/2 ≤255° +720°к -75°+360°к ≤ x/2≤75°+360°к
210°+360°к≤ x ≤510° +360°к -150°+720°к ≤ x≤150°+720°к
-150°+720°+720°к ≤ x ≤150°+720° +720°к
570°+720°к ≤ x ≤870°+720°к
Пошаговое объяснение:
cos² x/2 - sin² x/2 ≥- √3/2
cos² x/2 - (1-cos² x/2) ≥- √3/2
cos² x/2 - 1+cos² x/2 ≥- √3/2
2cos² x/2 ≥ 1 - √3/2
cos² x/2 ≥ 1/2 - √3/4
cos² x/2 ≥0,067 ±√ из обеих частей и потом применим арккосинус
cos x/2 ≤- 0,2588 cos x/2 ≥0,2588
105°+720°к≤ x/2 ≤255° +720°к -75°+360°к ≤ x/2≤75°+360°к
210°+360°к≤ x ≤510° +360°к -150°+720°к ≤ x≤150°+720°к
-150°+720°+720°к ≤ x ≤150°+720° +720°к
570°+720°к ≤ x ≤870°+720°к